2023
DOI: 10.1002/adma.202310143
|View full text |Cite
|
Sign up to set email alerts
|

Co/Mon Invigorated Bilateral Kinetics Modulation for Advanced Lithium–Sulfur Batteries

Yueyue Kong,
Lu Wang,
Muhammad Mamoor
et al.

Abstract: Sluggish sulfur redox kinetics and Li‐dendrite growth are the main bottlenecks for lithium–sulfur (Li–S) batteries. Separator modification serves as a dual‐purpose approach to address both of these challenges. In this study, the Co/MoN composite is rationally designed and applied as the modifier to modulate the electrochemical kinetics on both sides of the sulfur cathode and lithium anode. Benefiting from its adsorption‐catalysis function, the decorated separators (Co/MoN@PP) not only effectively inhibit polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In this type of heterojunction composite, it is commonly observed that the metal component plays a crucial role in facilitating fast electron migration, while the presence of polar materials contributes sufficient binding energy. This observation is consistent with previous studies. …”
Section: Resultssupporting
confidence: 94%
“…In this type of heterojunction composite, it is commonly observed that the metal component plays a crucial role in facilitating fast electron migration, while the presence of polar materials contributes sufficient binding energy. This observation is consistent with previous studies. …”
Section: Resultssupporting
confidence: 94%
“…After switching back to the current density of 0.5 C, the high capacity of 1010.2 mAh g À 1 is recovered. The rate performance of Sm-N 3 C 3 significantly exceeded that of NC and Sm 2 O 3 , as well as most of the reported cells using modified separators [52][53][54][55][56][57][58][59] (Figure 4g). Notably, Sm 2 O 3 shows the weakest catalytical effect on LiPSs conversion and poor battery performance, which is probably derived from high internal resistance and charge transfer resistance, as well as the strong adsorption of reactant molecules resulting the difficulty of migration in catalysis processing based on the discussion above.…”
Section: Methodsmentioning
confidence: 86%
“…Moreover, the LiPSs adsorbed on the separator can be reactivated and contribute to capacity retention [225]. In parallel with cathode engineering, extensive research has been conducted on metal compounds, heterostructures, and single-atom catalysts [226,227]. The introduction of these materials possessing both adsorption and catalytic capabilities significantly inhibit the LiPS shuttle effect, thereby preventing the diffusion of LiPSs to the Li metal anode and effectively protecting against Li corrosion caused by LiPS.…”
Section: Lips Adsorptionmentioning
confidence: 99%